Role of Lipoprotein-associated phospholipase A2 (Lp-PLA2) in prediction and assessment of the severity of coronary artery disease in patients with type 2 Diabetes Mellitus Short title: Lp-PLA2 and coronary artery disease: Lp-PLA2 and coronary artery disease - Kostovska, Irena; Cekovska, Svetlana; Tosheska Trajkovska, Katerina; Labudovic, Danica; Brezovska Kavrakova, Julijana; Topuzovska, Sonja; Ampova, Hristina; Emin, Melda; Petrushevska Stanojevska, Elena; Nedeska Minova, Natasa; Kostovski, Ognen; Boshev, Marjan (Journal of Medical Biochemistry, 2025)
Background: Lipoprotein-associated phospholipase A2 (Lp-PLA2) is a specific biomarker associated with an increased risk of coronary artery disease (CAD) development. This study aims to determine the relationship between Lp-PLA2 activity and the risk of development and severity of CAD in patients with type 2 Diabetes mellitus (T2DM).Methods: The cross-sectional study included 148 patients with T2DM, divided into two groups: patients with T2DM without confirmed CAD (n=56) and patients with T2DM and confirmed CAD (n=92), further divided into three subgroups based on the stage of CAD, and a control group of healthy individuals (n=44). Venous blood samples were collected from all participants to measure glucose, cholesterol, triglycerides, HDL, LDL, C-reactive protein, urea, and creatinine levels using standard photometric methods. Lp-PLA2 activity was measured using a chemiluminescent immunoassay method.Results: Patients with T2DM and confirmed CAD had significantly higher Lp-PLA2 levels than those without confirmed CAD and healthy individuals. A significant difference in Lp-PLA2 levels was found between the group without CAD, the patients with CAD divided into subgroups according to disease stage, and the healthy control group. A positive correlation was observed between Lp-PLA2 and BMI, glycated hemoglobin, total cholesterol, and HDL cholesterol. The optimal cutoff value for Lp-PLA2 < 250 ng/ml yielded a diagnostic sensitivity of 95.65% and specificity of 88.64% for patients with T2DM and diagnosed CAD.Conclusion: Lp-PLA2 can be used as a predictor for developing and assessing the severity of CAD in patients with T2DM.
Keywords: Lipoprotein-associated phospholipase A2, coronary artery disease, type 2 diabetes mellitus